An integrated tele-coupling analysis for requisition–compensation balance and its influence on carbon storage in China. (May 2022) - Gao, Runyi; Chuai, Xiaowei; Ge, Jingfeng; Wen, Jiqun; Zhao, Rongqin; Zuo, Tianhui
Abstract: The expansion of construction land and the reduction of farmland are two important aspects of land use change and land cover change (LUCC) that can greatly affect the terrestrial carbon balance. The requisition–compensation balance of farmland (RCBF) is an important land use policy in China, which aims to maintain the amount of farmland and prevent the unrestricted requisition of farmland for construction. This study has designed a new integrated tele-coupling framework to analyse the land use change and associated carbon storage change under the RCBF in China. The results show that on the national scale, although the quantitative balance of farmland has been achieved for the whole of China, the area of farmland in most provinces decreased, with a decrease in vegetation carbon (VC) storage of 3.7 Tg. For each province, this study finds that the more developed regions in the southeast of China have often acted as net importers, while some less developed regions have become primarily exporters with an evident expansion of construction land driven by other regions. The VC storage has decreased in most provinces due to the imbalance of farmland requisition and compensation and inappropriate compensation methods. In particular, some provinces located in the southwest of China have had the largest loss of VC storage due to their better hydrothermal conditions and relatively higher VC density. Thus, harmonious development and suitable compensation strategies, such as the farmland to forest program and environmental taxes, need to be further considered. Highlights: A new integrated framework of tele-coupling is designed. MRIO is used to quantify the virtual requisitioned farmland transfer among provinces. The vegetation carbon storage released 3.7 Tg during the implementation of RCBF. Inappropriate compensation for farmland will result in a great loss of carbon storage.